Evaluation of the accomplishment of goals of secondary care in oral health in the state of Sergipe - Santos Júnior, Leônidas Marinho dos (2020)
This study aims to evaluate the fulfillment of secondary care goals and the performance of Dental Specialty Centers in the state of Sergipe, Brazil. This is a quantitative and exploratory study, in which secondary data on the productivity of the year 2015 were collected from 11 CEOs, and compliance with secondary care was calculated and performance was obtained. The findings were associated with: type of dental specialty center, length of accreditation, population size, Municipal Human Development Index, population coverage of the Oral Health Team in the Family Health Strategy, type of management. Analysis was performed using the distribution of absolute and relative frequencies and Fisher's exact test. It was observed that the goals of primary care were observed in 81.9%, and the subgroup of specialty in 54.5% in Periodontics and 45.5% in Surgery. No municipality has met the goal in Endodontics. The results suggest the need to reorganize practices and qualify monitoring actions of oral health services, with a view to expanding specialized service offer.